Food and feed safety of a novel Vip3C insecticidal protein derived from Paenibacillus spp. for protection of crop plants against key Lepidopteran pests - Lucas J. McKinnon; Rong Wang; Cunxi Wang; Scott Saracco; Colton Kessenich; Virginia M. Johnson; Jennifer Calcaterra; Gregory Frierdich; Eric Bretsnyder; Luting Fang; Bingyao Li; Tianbo Xu (PLoS ONE, 2026)
Bacillus thuringiensis insecticidal proteins have been safely and effectively used for several decades as tools for insect pest control either as active ingredients in biopesticides or via transgenic expression in crop plants (GM crops). While the first generations of GM crops in the 1990s expressed only three-domain Cry proteins, GM corn and cotton varieties expressing vegetative insecticidal proteins from the Vip3 class began to be cultivated in the late 2000s (Vip3A). Here we describe a comprehensive food and feed safety assessment of Vip3Cb1, the first member of the Vip3C class to be expressed in commercial varieties of GM crops. Bioinformatic protein safety screens reiterate the placement of Vip3Cb1 as an insecticidal member of the Vip3 protein class and demonstrate a lack of homology to known allergens or toxins. In vitro characterization of the thermal stability and digestive fate demonstrates that dietary exposure to an intact, functional form of Vip3Cb1 is highly unlikely. Vip3Cb1 also showed no measurable effects in an in vivo acute oral toxicity study in mice. By weight of evidence, the bioinformatics assessments, in vitro and in vivo studies, history of safe use, and the previously reported mechanism of action similar to Vip3A collectively demonstrate no indication of a risk of Vip3Cb1 to the health of humans or animals and reinforces the overall safety of the Vip3 class of insecticidal proteins.